Ten pillars for the expansion of health system infection prevention capacity - Lisa K. Sturm; Tina R. Jacobs; Mohamad G. Fakih (Cambridge University Press, 2024)
The COVID-19 pandemic has accelerated changes in health care across the nation. Particularly, infection prevention programs have been subjected to pressures and increased responsibilities with no expansion in support. In addition, there is a rapid trend for health systems to merge to ensure long term sustainability. Based on our experience leading infection prevention at one of the largest health systems in the United States, we outline how systems can provide and increase capacity to optimize and enhance the hospital level infection prevention programs and outcomes. In this commentary, "Ten Pillars for the Expansion of Health System Infection Prevention Capacity" we offer 10 categories of what we have found to establish a successful and functioning infection prevention program. The pillars to support the infection prevention programs focus on structure, processes, empowerment, and partnerships, and the elements and strategies that comprise them.